Optaflexx1 affects rumen fermentation - Walker, Charles E.; Drouillard, James S.; Nagaraja, Tiruvoor G. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Three experiments were conducted to determine effects of ractopamine-HCl, sold under the trade name Optaflexx, on rumen fermentation. In experiment 1, fermentative gas production was measured in vitro to determine the impact of increasing amounts of ractopamine- HCl added to rumen fluid. Ractopamine-HCl increased gas production when added to rumen fluid up to 10 times the assumed physiological dosage of 200 mg per head/day, but depressed gas production at 100 times the physiological dose. Experiment 2 and 3 evaluated the effects of ractopamine-HCl on production of volatile fatty acids (VFAs) by ruminal microbes. In vitro experiments revealed no effect of ractopamine on volatile fatty acid production, but VFA levels in rumen fluid of cattle 23 hours after feeding were lower for cattle fed Optaflexx then for controls (P = 0.01). Results of these studies indicate that ractopamine-HCl has a direct influence on fermentation by rumen microflora.
Keywords: Beef; Cattle; Optaflexx; Ractopamine-HCl; volatile fatty acids (VFAs)